g-C3N4/CoAl-LDH 2D/2D hybrid heterojunction for boosting photocatalytic hydrogen evolution - Zhang, Jungang; Zhu, Qiaohong; Wang, Lingzhi; Nasir, Muhammad; Cho, So-Hye; Zhang, Jinlong (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this work, a 2D/2D heterojunction composed of CoAl layered double hydroxide (LDH) and graphitic carbon nitride nanosheets (CNNS) was designed and fabricated for boosting photocatalytic hydrogen generation. The as-prepared 20 mol% CoAl-LDH/CNNS exhibited a remarkable photocatalytic hydrogen evolution rate of 680.13 mu mol h(-1)g(-1), which was 21 times higher than that of pure CoAl-LDH (32.91 mu mol h(-1)g(-1)). The enhanced activity could be mainly attributed to its unique structure and high surface area. Distinct from ordinary heterojunction photocatalysts, two-dimensional (2D) heterojunctions with abundant 2D coupling interfaces and strong interfacial interaction could efficiently suppress the recombination of photo-induced charge carriers and shorten charge transmission distance. Particularly, compared with other concentrations, the increased surface area (138.70 m(2) g(-1)) of 20 mol% CoAl-LDH/CNNS, which is 3.94 times of pure CNNS (35.48 m(2)g(-1)) is more favorable for enhanced photocatalytic activity. Increasing the surface area of sheet-on-sheet heterostructure is an effective and novel strategy to facilitate the photocatalytic hydrogen evolution from water splitting. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: LAYERED DOUBLE HYDROXIDES; GRAPHITIC CARBON NITRIDE; HIGH-PERFORMANCE; H-2 EVOLUTION; BIFUNCTIONAL ELECTROCATALYST; 0D-2D HETEROJUNCTION; CHARGE SEPARATION; POROUS G-C3N4; EFFICIENT; WATER